the The Relationship Between Social Media Usage Intensity and Anxiety Levels Among Tarumanagara University Medical Students in 2025: The Relationship Between Social Media Usage Intensity and Anxiety Levels Among Tarumanagara University Medical Students in 2025 - Lourdes Thorino Beru Ginting; Lamhot Asnir Lumbantobin (CV. Jasa Sukses Abadi, 2025)
The rapid increase in social media use among university students has raised concerns regarding its potential psychological consequences, particularly anxiety disorders. This study aimed to determine the relationship between social media usage intensity and anxiety levels among medical students at the Faculty of Medicine, Tarumanagara University, in 2025. An analytical observational study with a cross-sectional design was conducted involving 212 respondents selected through consecutive sampling. Social media usage intensity was assessed using the Social Networking Time Use Scale (SONTUS), while anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS). Data were analyzed using the Spearman rank correlation test, and the strength of the association was estimated using the Prevalence Ratio (PR). The results showed that 65.6% of respondents had high to very high social media usage intensity, while 59.0% experienced moderate to severe anxiety. Spearman rank analysis demonstrated a statistically significant positive correlation between social media usage intensity and anxiety levels (r = 0.324; p < 0.001). Furthermore, students with high social media usage intensity had a 1.91-fold higher risk of experiencing moderate to severe anxiety than those with lower usage intensity. These findings indicate that excessive social media use may contribute to poorer mental health outcomes among medical students. Therefore, promoting awareness and providing education on responsible and mindful social media use is essential to reduce its adverse psychological effects, support healthy digital habits, and improve students' overall mental well-being.